2022
DOI: 10.1111/all.15582
|View full text |Cite
|
Sign up to set email alerts
|

RAB25 coordinates filaggrin‐containing keratohyalin granule maturation and affects atopic dermatitis severity

Abstract: Background: Keratohyalin granules (KHGs) supply the critical epidermal protein constituents such as filaggrin for maintaining skin barrier function during epidermal differentiation; however, their regulating mechanism remains largely unelucidated. Methods:To investigate the role of Ras-related protein Rab-25 (RAB25) expression in skin disease, we utilized skin specimens of patients with moderate-to-severe atopic dermatitis (AD) and healthy controls. To investigate the susceptibility of Rab25 knockout mice to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…RAB25, a promising severity biomarker, represents epidermal barrier function impairment in AD. 54 Recent study have shown that RAB25 expression in the skin is significantly lower in patients with AD. Moreover, RAB25 expression negatively correlated with the EASI score.…”
Section: Current Candidate Biomarkers Of Admentioning
confidence: 99%
See 2 more Smart Citations
“…RAB25, a promising severity biomarker, represents epidermal barrier function impairment in AD. 54 Recent study have shown that RAB25 expression in the skin is significantly lower in patients with AD. Moreover, RAB25 expression negatively correlated with the EASI score.…”
Section: Current Candidate Biomarkers Of Admentioning
confidence: 99%
“…It denotes an immunological hypersensitivity to Malassezia species Severity biomarker, Endotypic biomarker 48 , 49 Eosinophil counts, ECP Releases eosinophil basic proteins upon activation via Th2 cytokines Monitoring biomarker 50 , 51 Soluble IL-2R Soluble cytokine receptor which secreted upon T-cell activation. Elevated serum levels are observed across a range of immune-related conditions Monitoring biomarker 29 , 30 S100A7/A8/A9//A12 Anti-microbial peptides; preferentially kills E. coli Severity biomarker, 9 , 38 , 52 , 53 E-selectin Allows the adhesion of neutrophils, monocytes, and leukocytes on stimulated endothelium in the skin Monitoring biomarker 10 , 28 RAB25 A member of the RAB11 small GTPase subfamily, which orchestrates intracellular vesicle trafficking Severity biomarker 54 MMP8, 9, 12 Protease involved in macrophage migration, could also have a crucial role in regulating the resolution of inflammation Severity biomarker 10 , 38 , 41 , 55 LDH Tetrameric oxidoreductase enzyme; non-specific marker of tissue turnover Severity biomarker, Monitoring biomarker 28 , 56 CA II Carbonic anhydrase catalyses the reversible hydration of carbon dioxide Diagnostic biomarker 57 , 58 NELL2 Important for neuronal polarization and axon growth Diagnostic biomarker 58 EDN Secretory proteins of eosinophils, it has broad antiviral activity, targets RNA viruses …”
Section: Current Candidate Biomarkers Of Admentioning
confidence: 99%
See 1 more Smart Citation